1997
DOI: 10.1111/j.1651-2227.1997.tb14812.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism and insulin secretion in children with cyanotic congenital heart disease

Abstract: The aim of the study was to reveal differences in carbohydrate metabolism in children with cyanotic congenital heart diseases (CHD). Thirteen children with diseases of these kinds were investigated with regard to glucose tolerance and insulin secretion and comparisons were made with healthy controls of the same age. Investigations included an intravenous glucose tolerance test, insulin response to the glucose load in plasma and insulin secretion rate. The results reveal lower fasting glucose levels and signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…70 It would therefore be expected that a significant percentage of the population with moderate or complex ACHD will have diabetes mellitus or abnormal glucose metabolism. Of note, with regard to glucose management, the fasting glucose level in cyanotic patients may be lower because of the high resting catecholamine state and impaired nutritional status 71 ; however, there may concomitantly be increased clearance of insulin by the lung in right-to-left shunts.…”
Section: Prevalencementioning
confidence: 99%
“…70 It would therefore be expected that a significant percentage of the population with moderate or complex ACHD will have diabetes mellitus or abnormal glucose metabolism. Of note, with regard to glucose management, the fasting glucose level in cyanotic patients may be lower because of the high resting catecholamine state and impaired nutritional status 71 ; however, there may concomitantly be increased clearance of insulin by the lung in right-to-left shunts.…”
Section: Prevalencementioning
confidence: 99%
“…Hait et al 27) reported that glucose levels could be high in patients with a left-to-right shunt lesion such as ASD, VSD, and atrioventricular septal defect as well as even in cyanotic patients including those with Eisenmenger syndrome due to excessive clearance of insulin by the lungs. However, Lundell et al 28) suggested that cyanotic patients can also have lower glucose levels when fasting because of chronic increases in circulating catecholamines and poor nutrition. In our study, cyanotic patients including patients with Eisenmenger syndrome showed significantly higher glucose levels than those in the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, WHR, HOMA-IR, serum C-peptide levels were found to be non-significant when compared to controls. This may be due to increase of catecholamine in circulation [20].…”
Section: Discussionmentioning
confidence: 99%